2020
DOI: 10.4049/jimmunol.1901472
|View full text |Cite
|
Sign up to set email alerts
|

Direct Antiviral Activity of IFN-Stimulated Genes Is Responsible for Resistance to Paramyxoviruses in ISG15-Deficient Cells

Abstract: IFNs, produced during viral infections, induce the expression of hundreds of IFN-stimulated genes (ISGs). Some ISGs have specific antiviral activity, whereas others regulate the cellular response. Besides functioning as an antiviral effector, ISG15 is a negative regulator of IFN signaling, and inherited ISG15 deficiency leads to autoinflammatory IFNopathies, in which individuals exhibit elevated ISG expression in the absence of pathogenic infection. We have recapitulated these effects in cultured human A549-IS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Holthaus et al . confirmed that virus resistance in ISG15 −/− cells was due to the overexpression of viral restriction factors [114]. Because cells are resistant to infection, they are phenotypically silent and not detectable by FACS when infected with a reporter virus; deletion of a restriction factor, even one with low to moderate activity, results in a detectable signal that would be otherwise missed.…”
Section: Choosing a Screening Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Holthaus et al . confirmed that virus resistance in ISG15 −/− cells was due to the overexpression of viral restriction factors [114]. Because cells are resistant to infection, they are phenotypically silent and not detectable by FACS when infected with a reporter virus; deletion of a restriction factor, even one with low to moderate activity, results in a detectable signal that would be otherwise missed.…”
Section: Choosing a Screening Methodsmentioning
confidence: 87%
“…One possibility might be to use cells deficient in IFN stimulated gene 15 (ISG15); these cells, when treated with IFN-α, exhibit an overamplified IFN response resulting in the overexpression of ISGs and, subsequently, a greater ability to resist virus infection. Holthaus et al confirmed that virus resistance in ISG15 −/− cells was due to the overexpression of viral restriction factors [114]. Because cells are resistant to infection, they are phenotypically silent and not detectable by FACS when infected with a reporter virus; deletion of a restriction factor, even one with low to moderate activity, results in a detectable signal that would be otherwise missed.…”
Section: Choosing a Screening Methods Advantages And Disadvantages Of Screening Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In protein synthesis ISG15 can inhibit translation of individual proteins through modification of RNA-binding partners [ 118 ], as well as by suppressing global or mRNA-specific translation via ISGylation of key translational regulators ( Figure 3 , Section 6) [ 36 , 119 , 120 ]. This activity is largely thought to be an antiviral mechanism whereby translation of newly synthesized viral proteins is restricted via translational suppression following IFN stimulation.…”
Section: Isg15: More Than An Antiviral Proteinmentioning
confidence: 99%
“…Several reports now show that inherited ISG15-deficiency in humans causes type I interferonopathy and autoinflammatory disease (17)(18)(19). ISG15-deficient cells exhibited enhanced and prolonged ISG expression and a concomitant resistance to virus infection (18,20,21) a phenotype also associated with USP18 deficiency (13,22). Indeed, despite high levels of USP18 transcription, USP18 protein levels in ISG15-deficient cells are very low (18,20,21) and previous reports have shown that intracellular ISG15 is required for rescuing USP18 from S-phase kinase associated protein 2 (SKP2)-mediated proteasomal degradation (18,23).…”
Section: Introductionmentioning
confidence: 99%